Rodzinny kapitał społeczny a wzrost gospodarczy w Polsce - Sztaudynger, Jan Jacek (Annales. Etyka w Życiu Gospodarczym, 2009)
Economic growth is mostly explained by investments and employment growth. Since the mid 1990s various social categories have been introduced into the economic growth analysis such as trust, crime and income inequality etc.According to sociology and psychology, it is the family that constitutes interpersonal ties and is an indicator of happiness and quality of life. It can be said that happy people better fulfil their social roles and also work better. We set a hypothesis that the family ties have an influence on economic growth. More precisely: the more divorces (compared to newly couples), the slower economic growth. This hypothesis was confirmed in an analysis of Poland’s economy in the years 1967–2006. Due to the disintegration of family ties measured by the above mentioned divorce rate Poland’s annual economic growth was slowed by about a 0.6 percentage point on average. This estimation is based on a GDP growth model which, along with the divorce rate, also includes employment dynamics, invest rate and crime rate.